Predictors of suicidal ideation in Korean American older adults: analysis of the Memory and Aging Study of Koreans (MASK). (25th October 2016) - Na, Peter J.; Kim, Kim B.; Lee‐Tauler, Su Yeon; Han, Hae‐Ra; Kim, Miyong T.; Lee, Hochang B.
Abstract : Objective: Our aim is to investigate the prevalence and predictors of suicidal ideation among Korean American older adults and assess the self‐rated mental health of Korean American older adults with suicidal ideation with or without depressive syndrome. Methods: The Memory and Aging Study of Koreans is a cross‐sectional, epidemiologic study of a community‐representative sample of Korean American older adults ( N = 1116) residing in the Baltimore–Washington area. Participants were interviewed using the Korean version of the Patient Health Questionnaire (PHQ‐9K). In addition, demographic information, self‐rated mental health, and self‐rated physical health status were obtained. Results: In this study, 14.7% of Korean American older adults reported suicidal ideation. Predictors of suicidal ideation included living alone, major or minor depressive syndrome (diagnosed by the PHQ‐9K), shorter duration of residency in the USA, and poorer self‐rated mental health status. Of those who reported suicidal ideation, 64% did not have minor or major depressive syndrome. However, their self‐rated mental health was as poor as that of those with major or minor depressive syndrome but without suicidal ideation. Conclusion: Suicidal ideation without depressive syndromes was common among Korean American older adults. For this group of elders with poor self‐rated mental health, future studies should look to improving early detection of suicide risks and developing feasible suicide prevention interventions. Copyright © 2016 John Wiley & Sons, Ltd.